Steatotic liver disease in people with HIV at Tshepong Hospital: A post-mortem analysis - Aqeela Moosa; Ebrahim Variava; Alistair D. Calver; Gajendra Chita; Nadia Sabet; Sharol Ngwenya; Maria Papathanasopoulos; Tanvier Omar (Southern African Journal of HIV Medicine)
Background: Liver disease is the leading cause of non-AIDS-related mortality in people living with HIV (PLWH). Steatotic liver disease (SLD) is increasingly recognised as an important aetiological factor in liver dysfunction in PLWH.